(untitled) (KYAMC Journal, 2021)
Background: Nephrotic syndrome is one of most common renal disease in childhood and infection is one of the most important complication in this disease. Infection increase the mortality and morbidity of this type of patients. Most common infection is UTI. So through this study we can able to determine biochemical difference between childhood nephrotic syndrome with Urinary Tract Infection (UTI) and with out UTI patients and its clinical significance. Objective: To determine the biochemical different in childhood nephrotic syndrome patients and its relation with urinary tract infection. Materials and Methods: It is prospective study done in pediatric department in Rajshahi Medical College Hospital, 60 patient of both sex age between 1-12 years, diagnosed as idiopathic nephrotic syndrome with and without UTI were included in this study. Data collection ware done by history taking, clinical examination, laboratory investigations and followed up. Patients were followed up till cure of UTI and remission of proteinuria. After data collection statistical analysis were done by computerized software. Results: In our study we found there were biochemical difference between childhood nephrotic syndrome with UTI and without UTI patients. In patients of nephrotic syndrome with UTI serum albumin decrease significantly and serum cholesterol increase significantly than nephritic syndrome without UTI patients. Conclusion: Child with nephrotic with UTI patients had lower serum albumin and higher serum cholesterol than nephrotic syndrome without UTI patients and it effect the morbidity mortality of this patients. KYAMC Journal.2021;12(1): 22-25